The Epidemiology, Molecular, and Clinical of Human Adenoviruses in Children Hospitalized With Acute Respiratory Infections - Wen, Shunhang; Lin, Zupan; Zhang, Yue; Lv, Fangfang; Li, Haiyan; Zhang, Xueya; Lin, Li; Zhu, Hui-Hui; Xu, Zhi; Li, Changchong; Zhang, Hailin (Frontiers in Microbiology, 2021)
Introduction Human adenovirus (HAdV) is a common pathogen in children with acute respiratory infections (ARIs). The aim was to describe the epidemiology, molecular, and clinical characteristics of HAdV among children hospitalized with ARIs in Wenzhou in southeastern China. Methodology From January 2018 to December 2019, nasopharyngeal swab or sputum specimens were prospectively collected from hospitalized children with ARIs. HAdV was detected using direct immunofluorescence. We used a multiplex PCR assay combined with capillary electrophoresis targeting the hexon gene’s hypervariable region to identify HAdV types 1, 2, 3, 4, 5, 7, 14, 21, 37, 40, 41, and 55. We analyzed the epidemiological, molecular, and clinical data according to the HAdV type. Results HAdVs were detected in 1,059 (3.5%) of the total of 30,543 children tested. A total of 947 cases with monotype HAdV identified by the PCR assay were included in the analysis. HAdV-3 (415/947, 43.8%), HAdV-7 (318/947, 33.6%), HAdV-2 (108/947, 11.4%), and HAdV-1 (70/947, 7.4%) were the predominant types. Of the 550 (58.1%) cases detected from December 2018 to August 2019, HAdV-3, and HAdV-7 were the main types. The main diagnoses included 358 cases of pneumonia, 232 cases of tonsillitis, 198 cases of bronchitis, and 159 cases of upper respiratory tract infection (URTI). Among children with pneumonia the main types were HAdV-7 (51.1%), HAdV-3 (36.9%), and HAdV-1 (2.2%). Among children with bronchitis, the main types were HAdV-3 (48.0%), HAdV-7 (28.3%), and HAdV-2 (10.6%). Among children with URTIs, the main types were HAdV-3 (49.7%), HAdV-7 (22.6%), and HAdV-2 (13.2%). Among children with tonsillitis, the main types were HAdV-3 (47.4%), HAdV-2 (22.4%), and HAdV-7 (18.5%). In total, 101 (55.2%) patients required supplemental oxygen, 15 (8.2%) required critical care, and 1 child (0.5%) with HAdV-7 pneumonia died. Conclusion HAdV-3 -7, -2, and -1 were the predominant types identified in hospitalized children with ARIs in Wenzhou. From December 2018 to August 2019, there were outbreaks of HAdV-3 and -7. There were significant differences in HAdV types among children with pneumonia, tonsillitis, bronchitis, and URTI. HAdV-7 can cause more severe pneumonia in children than HAdV-3.